Pre-hospital delay, clinical characteristics, angiographic findings, and in-hospital mortality in young and middle-aged adults with acute coronary syndrome: a single-centre registry analysis - Bauer, Dávid; Neuberg, Marek; Nováčková, Markéta; Kočka, Viktor; Toušek, Petr (European heart journal supplements, 2023)
There are several differences between younger and older adults with acute coronary syndrome (ACS). However, few studies have evaluated these differences. We analysed the pre-hospital time interval [symptom onset to first medical contact (FMC)], clinical characteristics, angiographic findings, and in-hospital mortality in patients aged ≤50 (group A) and 51-65 (group B) years hospitalised for ACS. We retrospectively collected data from 2010 consecutive patients hospitalised with ACS between 1 October 2018 and 31 October 2021 from a single-centre ACS registry. Groups A and B included 182 and 498 patients, respectively. ST-segment elevation myocardial infarction (STEMI) was more common in group A than group B (62.6 and 45.6%, respectively; P < 0.001). The median time from symptom onset to FMC in STEMI patients did not significantly differ between groups A and B [74 (40-198) and 96 (40-249) min, respectively; P = 0.369]. There was no difference in the rate of sub-acute STEMI (symptom onset to FMC > 24 h) between groups A and B (10.4% and 9.0%, respectively; P = 0.579). Among patients with non-ST elevation acute coronary syndrome (NSTE-ACS), 41.8 and 50.2% of those in groups A and B, respectively, presented to the hospital within 24 h of symptom onset (P = 0.219). The prevalence of previous myocardial infarction was 19.2% in group A and 19.5% in group B (P = 1.00). Hypertension, diabetes, and peripheral arterial disease were more common in group B than group A. Active smoking was more common in group A than group B (67 and 54.2%, respectively; P = 0.021). Single-vessel disease was present in 52.2 and 37.1% of participants in groups A and B, respectively (P = 0.002). Proximal left anterior descending artery was more commonly the culprit lesion in group A compared with group B, irrespective of the ACS type (STEMI, 37.7 and 24.2%, respectively; P = 0.009; NSTE-ACS, 29.4 and 21%, respectively; P = 0.140). The hospital mortality rate for STEMI patients was 1.8 and 4.4% in groups A and B, respectively (P = 0.210), while for NSTE-ACS patients it was 2.9 and 2.6% in groups A and B, respectively (P = 0.873). No significant differences in pre-hospital delay were found between young (≤50 years) and middle-aged (51-65 years) patients with ACS. Although clinical characteristics and angiographic findings differ between young and middle-aged patients with ACS, the in-hospital mortality rate did not differ between the groups and was low for both of them.
Keywords: Symptom onset; Angiographic findings; Young adults; Acute coronary syndrome; First medical contact; In-hospital mortality